Biological Carbon Pump Sequestration Efficiency in the North Atlantic: A Leaky or a Long‐Term Sink?. Issue 6 (13th June 2022) - Baker, Chelsey A.; Martin, Adrian P.; Yool, Andrew; Popova, Ekaterina
Abstract: The North Atlantic Ocean is a key region for carbon sequestration by the biological carbon pump (BCP). The quantity of organic carbon exported from the surface, the region and depth at which it is remineralized, and the subsequent timescale of ventilation (return of the remineralized carbon back into contact with the atmosphere), control the magnitude of BCP sequestration. Carbon stored in the ocean for >100 years is assumed to be sequestered for climate‐relevant timescales. We apply Lagrangian tracking to an ocean circulation and marine biogeochemistry model to determine the fate of North Atlantic organic carbon export. Organic carbon assumed to undergo remineralization at each of three vertical horizons (500, 1, 000, and 2, 000 m) is tracked to determine how much remains out of contact with the atmosphere for 100 years. The fraction that remains below the mixed layer for 100 years is defined as the sequestration efficiency (SEff) of remineralized exported carbon. For exported carbon remineralized at the 500, 1, 000 and 2, 000 m horizons, the SEff is 28%, 66% and 94%, respectively. Calculating the amount of carbon sequestered using depths ≤1, 000 m, and not accounting for downstream ventilation, overestimates 100‐year carbon sequestration by at least 39%. This work has implications for the accuracy of future carbon sequestration estimates, which may be overstated, and for carbon management strategies (e.g., oceanic carbon dioxide removal and Blue Carbon schemes) that require long‐term sequestration to be successful. Plain Language Summary: The North Atlantic Ocean is a key region for carbon uptake and organic carbon storage in the interior ocean for climate‐relevant timescales (>100 years). Sinking organic carbon that reaches the interior ocean is respired there to form dissolved inorganic carbon. The fate of this carbon, that is, whether it remains in the ocean interior or returns to the surface and is ventilated to the atmosphere, depends on its physical circulation pathways. To investigate the efficiency of carbon storage in the North Atlantic Ocean we released virtual particles at three different starting depths (500, 1, 000 and 2, 000 m) into a global ocean model and tracked the pathways they followed for 100 years. 66% of virtual particles released at 1, 000 m depth remained out of contact with the atmosphere for 100 years. Combining this pathway analysis with observation‐ and model‐derived geographical fields of sinking carbon flux, we estimate that the 100‐year North Atlantic carbon storage may be overestimated by 39% at 1, 000 m because of this ventilation to the atmosphere. These findings have important implications for accurately estimating future ocean carbon storage. In particular, for carbon management strategies that require long‐term sequestration to be successful (e.g., oceanic carbon dioxide removal and Blue Carbon schemes). Key Points: Lagrangian simulations show that North Atlantic Ocean sequestration efficiency of remineralized exported carbon (REC) varies strongly by region Only 66% of North Atlantic REC at 1, 000 m will remain out of contact with the atmosphere for 100 years Fixed sequestration horizons ≤1, 000 m can significantly overestimate long‐term carbon sequestration